2019
DOI: 10.1177/0731684419873712
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of tensile strength and dimensional variation of T700 carbon fibres using an improved experimental setup

Abstract: Knowledge of fibre strength is crucial for understanding the failure behaviour of fibre-reinforced composite materials and structures. Measuring the properties of technical fibres has been known to be very challenging, and the different challenges associated with single fibre characterisation are illustrated in this article. An improved and automated experimental methodology for tensile testing of single fibres is described. This process has been used to generate fibre strength data for T700 carbon fibres at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The variation in the measured mechanical properties of the CF at all misalignment angles is consistent with the results of CF tensile testing in other studies [17,25,26] as indicated by the experimental coefficients of variance (CV%) in table 1. Experimentally determined mechanical properties and coefficients of variance for CF at misalignment angles of 0 5 • , 10 • , 15 • , and 20 • .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The variation in the measured mechanical properties of the CF at all misalignment angles is consistent with the results of CF tensile testing in other studies [17,25,26] as indicated by the experimental coefficients of variance (CV%) in table 1. Experimentally determined mechanical properties and coefficients of variance for CF at misalignment angles of 0 5 • , 10 • , 15 • , and 20 • .…”
Section: Discussionsupporting
confidence: 89%
“…Recent single-fiber tensile testing of commercial CFs (Toray, T700) has shown that there is no correlation between fiber diameter and mechanical properties [17]. Therefore, measuring the diameter of each fiber will reduce the standard deviation in tensile modulus and tensile strength, but it will not change the average result given that the fiber diameters follow a normal distribution, as illustrated by the Gaussian shape of the histogram and the linearity of the quantile-quantile plot (figures 1(c) and (d)).…”
Section: Carbon Fibersmentioning
confidence: 99%
“…Material imperfections explain this difference to a large extent. Fibre surface defects, among other imperfections, lead to a stochastic fibre strength commonly modelled by a Weibull distribution [3]. In combination with, for example, misaligned fibres [4][5][6], unevenly distributed [2] fibres or voids [7] in the matrix material this affects the stochastic behaviour of composite structures.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have emphasised the importance of testing a sufficient number of fibres to be able to determine the Weibull parameters accurately [10,11]. Other authors identified experimental issues in single fibre tensile testing, such as fibre alignment [12][13][14], fibre diameter variation [12,14] and stress concentrations associated to fibre gripping [15]. Other hypotheses have also been raised, such as whether the strength of fibres embedded in a resin is different from the one measured in bare fibre tests, but these remain unproven [16].…”
Section: Introductionmentioning
confidence: 99%